The Relationship of Visual Support Toward The Clinical Improvement In Children With Autism Spectrum Disorders - Tiwik Koesdiningsih; Lestari Basoeki; Nining Febriyana; Margarita Maria Maramis (Jurnal Berkala Epidemiologi, 2019)
Background: The prevalence of autism spectrum disorders (ASD) has increased in the last 30 years from 0.04 to 0.50. This condition increase the parents’ awareness and understanding in early diagnosis, education, management and health services for children with ASD. Purpose: This study aims to analyze the relationship between the uses of visual support for clinical improvement of children with ASD. Method: This study is an observational analytic study. The research was conducted at UPTD ABK Sidoarjo from March to June 2018. The research subjects in this study were four to seven years children with ASD condition. The sampling technique was consecutive sampling and was accomplished during the pre-test and post-test design. The measurement tool for using the Indonesian version of childhood autism rating scale (CARS) that has been validated. Management of visual support has been done for 120 minutes in three months (12 times) consisted of six activities, each activity for 20 minutes with one-one technique (one subject with one therapist). Results: There was no relationship improvement of the  CARS based on the pre and post visual support management for three months (12 times) on general impression data, level, and consistency of intellectual responses. The results of paired t-test on the pre and post visual support management for three months (12 times) showed decreasing value of CARS. This result means that social, communication and psychomotor interactions have p<0.01. Conclusion: Management of visual support is associated with clinical improvement in social interaction, communication (non-verbal) and psychomotor (especially gross motoric).